Contemporary Approaches to Mixed Methods–Grounded Theory Research: A Field-Based Analysis. (April 2019) - Guetterman, Timothy C.; Babchuk, Wayne A.; Howell Smith, Michelle C.; Stevens, Jared
Key scholars have lauded benefits of integrating mixed methods and grounded theory—or mixed methods–grounded theory (MM-GT)—yet there have been few attempts to ascertain in what ways researchers use MM-GT. Our aim was to systematically, but not exhaustively, examine applications of MM-GT and offer procedural guidelines. We identified 61 empirical MM-GT articles and developed a codebook for analysis. MM-GT was widely used across disciplines. Most published MM-GT provided little methodological detail regarding grounded theory, mixed methods, and their integration; theoretical development was noticeably absent; and the majority followed a convergent mixed methods design. This inquiry contributes to emerging discussions regarding the ways in which MM-GT can or should be used to more fully realize the potential of this approach.